Clinico-epidemiology and aetiopathogenesis of gallstone disease in the South Asian region: a scoping review protocol - Harshi Weerakoon; Ishari Vithanage; Oshadhi Alahakoon; Kosala Weerakoon (BMJ Open)
Introduction Pathogenesis of gallstones (GS) is multifactorial and is influenced by numerous environmental and genetic risk factors. As a result, clinico-epidemiology and aetiopathogenesis of GS vary in different populations. Understanding the aetiopathogenesis of GS for different populations is imperative in control and prevention of GS disease and its associated complications. This protocol describes the methodology of a scoping review which focuses on synthesising the most updated knowledge on GS disease in South Asia.Methods and analysis The scoping review proposed in this protocol will be guided by Arksey and O’Malley’s framework and the Joanna Briggs Institute Reviewers’ Manual. Accordingly, population, concept and context strategy will be used to formulate the scoping review question, eligibility criteria and search strategy. In the search, electronic databases, MEDLINE/PubMed, ScienceDirect, Scopus, Cochrane library, CINAHL, Trip, and Google scholar, as well as various grey literature sources will be used in synthesising and presenting the findings on clinico-epidemiology and aetiopathogenesis of GS disease in South Asia.Ethics and dissemination As secondary data will be used in the study, ethical approval will not be required. The scoping review proposed by this protocol will accurately summarise the current knowledge on GS disease in South Asia based on published and unpublished literature on the field. Thus, the evidence presented in the review will be important for healthcare providers to make decisions on the control and prevention of GS disease and as well as to identify future research priorities on GS disease in South Asia.